LC‐MS/MS method for the differential diagnosis of treatable early onset inherited metabolic epilepsies. Issue 5 (16th May 2020) - Mathis, Déborah; Beese, Karin; Rüegg, Carmen; Plecko, Barbara; Hersberger, Martin
Abstract: Rapid diagnosis and early specific treatment of metabolic epilepsies due to inborn errors of metabolism (IEMs) is crucial to avoid irreversible sequalae. Nowadays, besides the profile analysis of amino‐ and organic acids, a range of additional targeted assays is used for the selective screening of those diseases. This strategy can lead to long turn‐around times, repeated sampling and diagnostic delays. To replace those individual targeted assays, we developed a new liquid chromatography mass spectrometry method (LC‐MS/MS) for the differential diagnosis of inherited metabolic epilepsies that are potentially treatable. The method was developed to simultaneously quantify 12 metabolites (sulfocysteine, guanidinoacetate, creatine, pipecolic acid, Δ 1 ‐piperideine‐6‐carboxylate (P6C), proline, Δ 1 ‐pyrroline‐5‐carboxylate (P5C), and the B6 ‐vitamers) enabling the diagnosis of nine different treatable IEMs presenting primarily with early‐onset epilepsy. Plasma and urine samples were mixed with internal standards, precipitated and the supernatants were analyzed by LC‐MS/MS. In comparison with previous assays, no derivatization of the metabolites is necessary for analysis. This LC‐MS method was validated for quantitative results for all metabolites except P6C and P5C for which semiquantitative results were obtained due to the absence of commercially available standards. Coefficients of variation for all analytes were below 15% and recovery rates range between 80% and 120%. Analysis of patient samples with known IEMs demonstrated the diagnostic value of the method. The presented assay covers a selected panel of biochemical markers, improves the efficiency in the laboratory, and potentially leads to faster diagnoses and earlier treatment avoiding irreversible damage in patients affected with IEMs.